Perlindungan Hukum Bagi Investor Indonesia pada Perusahaan Joint Venture dalam Perusahaan Penanam Modal Asing - Welfin, Deni (UNES Law Review, 2023)
To increase economic competitiveness in the international world. Indonesia needs capital assistance, one of which is from foreign investors. There have been many regulations issued by the government to provide aspects of legal certainty and ease of investment in order to attract foreign investors into Indonesia. As one of the ways investors enter and invest their funds in Indonesia is by using the Joint Venture method. In foreign investment, disputes may arise between local and foreign partners. Thus, Indonesia also needs to provide a sense of security and legal protection for domestic investors so as not to experience pressure in the country due to the effects of differences in capital capabilities. Regulations regarding legal protection for minority investors in Joint Venture agreements are not expressly accommodated in Law Number 25 of 2007 concerning Investment. Law Number 25 of 2007 concerning Investment requires foreign investors to form a Limited Liability Company. Therefore, all regulations regarding the rights and obligations of shareholders can be accommodated in Law Number 40 of 2007 concerning Limited Liability Companies. However, if the parties to the Joint Venture contract make other agreements outside of Law Number 40 of 2007 concerning Limited Liability Companies, the provisions in Law Number 40 of 2007 concerning Limited Liability Companies will no longer apply.